Hochpräzise Bestimmung eines astrogeodätischen Quasigeoidprofils im Harz für die Validierung des Quasigeoidmodells GCG05 - Hirt, Christian; Feldmann-Westendorff, U.; Denker, H.; Flury, J.; Jahn, C.; Lindau, A.; Seeber, G.; Voigt, C. (Wittwer, 2008)
This paper deals with the determination of a high-precision astrogeodetic quasigeoid profile for the validation of the gravimetric quasigeoid model GCG05 in the Harz mountains in Northern Germany. The Hannover Digital Zenith Camera System TZK2-D was used for the observation of new vertical deflection data at densely spaced stations (500-600 m averagestation spacing) along a 63 km long traverse over the Harz mountains. For the computation of the astrogeodetic quasigeoid profile, the method of astronomical-topographic levelling was applied, using digital terrain model data for the interpolation of vertical deflections. The accuracy of the astrogeodetic quasigeoid profile has been estimated to be about 1.5-2 mm. The comparison between the astrogeodetic solution and the gravimetric model GCG05 shows a RMS error of about 3 mm and maximum differences of 7 mm.